Laparoscopic Salpingectomy for Isolated Fallopian Tube Torsion in the Third Trimester - R. P. Duncan; M. M. Shah (Case Reports in Obstetrics and Gynecology)
Isolated tubal torsion is a rare event. The clinical presentation is often nonspecific and the diagnosis is difficult, especially in the gravida abdomen. If left untreated, torsion can result in premature labour and foetal loss, as well as maternal morbidity. Here we present a case of isolated tubal torsion in a primigravida occurring in her third trimester and subsequent successful laparoscopic salpingectomy, rather than laparotomy. We discuss some of the diagnostic difficulties faced and approached to surgery as well as a brief review of the literature. In our case the women went on to successfully complete her pregnancy with no further complications.